2017
DOI: 10.1177/0972150917692196
|View full text |Cite
|
Sign up to set email alerts
|

Functional Foods: The New Secret of the Health Conscious Indian Women!!

Abstract: In India, with growing disposable income and increased urbanization and health consciousness among people, the demand for functional foods is emerging. Consumers are more proactive about their health and this in turn has stirred the global market for functional foods and beverages. This article attempts to segment consumers using cluster analysis on the basis of their health orientation and perception towards functional foods. Correlation has been employed to measure the relation between health orientation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Global consumption and the market for functional foods pertain to, in large, consumers’ health consciousness [ 1 ] and their awareness, as well as knowledge [ 2 ]. As a result, studies that correlate between consumers’ knowledge in functional foods and their physical health are of great interest to researchers [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Global consumption and the market for functional foods pertain to, in large, consumers’ health consciousness [ 1 ] and their awareness, as well as knowledge [ 2 ]. As a result, studies that correlate between consumers’ knowledge in functional foods and their physical health are of great interest to researchers [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consumers’ health consciousness and the necessity for functional foods are significantly correlated [ 1 ]. A recent study by Nahid [ 7 ] reported that health awareness is the only factor that influences the purchase intent of both processed and raw LM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kareklas, Carlson, and Muehling (2014) provided a theoretical assessment on the factors influencing consumer purchase behaviour for organic food products. Kapoor and Munjal (2017) segmented Indian Women consumers using cluster analysis based on their health orientation and perception towards functional foods. Azam, Othman, Musa, Fatah, and Awal (2012) analysed the factors affecting purchase intentions of the consumers for organic food products using primary consumer survey of 250 respondents in Malaysia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Empirical studies provide sufficient evidences on implication of demographic variables on purchase decisions (Cranfield, Henson, & Masakure, 2011;Goetzke & Spiller, 2014;Kapoor & Munjal, 2017;Petrovičová, 2009). Product and market attributes are other set of variables affecting the purchase decisions for healthy food products (Azam et al, 2012;Suh, Eves, & Lumbers, 2012).…”
Section: Conceptual Research Frameworkmentioning
confidence: 99%